PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH (Survei pada Pemerintah Daerah Se-Eks. Karesidenan Surakarta) - Santoso, Heru Mulyadi; Sarwono, Aris Eddy; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
â€œThis research was conducted on the Ex-Regional Government. Surakarta residency consists of 6 districts and 1 municipality, the type of data used is quantitative data. Data sources used are primary and secondary data. The entire population in this study were all Ex-Regional Government employees. Surakarta Residency. The sample used in this study is an employee of the Local Government accounting field. Surakarta Residency. The sampling technique is done by using purposive sampling method. In this study, referring to government accounting standards, human resource competencies and the use of information technology are important for the quality of financial reporting.â€